The extent of internal auditors’ commitment to efficiency in accordance with international standards issued by (IIA) and its reflection on the effectiveness of audit committees (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to demonstrate the extent of internal auditors’ commitment to the efficiency standard issued by (IIA) and its impact on the effectiveness of audit committees in the Iraqi banking system. In the practical aspect, the researcher relied on the descriptive analytical approach by adopting (the checklist), which included a set of questions that fit with the problem, importance and hypothesis of the research, and was distributed to members of the Internal Audit Department at the Central Bank of Iraq as a sample for the research to reach and interpret the results, as it was distributed after evaluating them. It was judged by a number of specialists, which amounted to (61) forms, and (59) forms were returned. The results of the field study were analyzed and the hypotheses were tested using the statistical analysis program (SPSSvr.24). The research reached a set of results, the most important of which are: Internal auditors at the Central Bank of Iraq are committed to efficiency in accordance with international standards issued by (IIA) when performing their duties, through improvement. And the continuous development of their experience and skills by adopting the latest courses that keep pace with developments in the profession and international standards in a way that guarantees the quality of the work they perform. The research also included a number of recommendations, the most important of which are: The need for the Audit Committee to monitor the adequacy of the amounts allocated for training and developing internal audit in the annual budget of the Central Bank and recommend increasing them if necessary. This contributes to achieving the internal auditor’s commitment to competence in accordance with international standards issued by (IIA) and ensuring continuous improvement of his cognitive and professional skills